Effects of incorporation of nanoparticles into dental acrylic resins on antimicrobial and physico-mechanical properties: A meta-analysis of in vitro studies - Maryam Pourhajibagher; Abbas Bahador (Elsevier, 2022)
Background: A meta-analysis study was conducted to determine whether the incorporation of nanoparticles into the dental acrylic resins inﬂuence the physico-mechanical properties and whether there are the appropriate nanoparticles exhibiting excellent antimicrobial activity against cariogenic bacteria along with acceptable physico-mechanical properties. Methods: We systematically searched the various databases up to December 2021. The review was performed based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and the Consolidated Standards of Reporting Trials (CONSORT) guidelines. A meta-analysis of physico-mechanical properties was performed by a random-effects model at a 95% confidence interval and the antimicrobial effects were analyzed descriptively. Results: 27 studies were included for the final analysis. There was no statistically significant difference in flexural strength (0.553, [95% confidence interval (CI) 0.501-0.604]), microhardness (0.509, [95% CI 0.278-0.736]), surface roughness (0.753, [95% CI 0.315-0.953]), impact strength (0.90, [95% CI 0.188-0.997]), and elastic modulus (0.848, [95% CI 0.514-0.967]), with nanoparticles addition compared with the control group. Forest plots were not generated for the thermal conductivity, tensile strength, and translucency because of the lack of comparison. Although the articles showed high heterogeneity without the high risk of bias, the finding showed the nanoparticles at low concentrations into dental acrylic resins could improve the antimicrobial activities without adverse effects on their physico-mechanical properties. Conclusion: Adding the low concentration of nanoparticles such as 0.5% Ag, ≤0.25% TiO2, and ≤0.25% SiO2 as the most abundant antimicrobial nanoparticles do not influence their physico-mechanical properties and can be effective in the elimination of cariogenic pathogens.